The Impact of the COVID-19 Pandemic on the Intensive Care Residency Program in Portugal - Rebelo, Carla (2022)
Introduction: In 2020, critical care departments underwent profound changes imposed by the COVID-19 pandemic. The aim of this study was to evaluate the impact of the pandemic on the intensive care residency program in Portugal.Material and Methods: The Association of Critical Care Residents (AIMINT) prepared a questionnaire using the Google Forms® tool, which was applied during August 2020 to the Critical Care residents in Portugal. A descriptive analysis was performed with the data collected.Results: Eighty-five residents participated in the questionnaire, yieldinga response rate of 62%. Three-quarters of all participants provided care to COVID-19 patients. More than 80% of the surveyed participants were on rotations, and these were canceled in 59% of cases. Seventy-eight percent reported a workload greater than 40 hours per week.Conclusion: The COVID-19 pandemic had an impact on the Critical Care Residency program in Portugal. Most residents surveyed provided care to COVID-19 patients and not only saw their rotations suspended but also experienced difficulties in rescheduling them.